A Rare Fatal Case of COVID-19 Co-Infection with Community-Acquired Methicillin-Resistant Staphylococcus Aureus in a Diabetic Patient - Meng Z; Wuxiuer R; Zhao F; Yang Q (Infection and Drug Resistance)
Zhaolu Meng,1 Rehanguli Wuxiuer,1 Feng Zhao,2 Qiao Yang1,3 1Department of Infectious Diseases, Sir Run Run Shaw Hospital, Alaer Hospital, Zhejiang University School of Medicine, Alaer, 843300, People’s Republic of China; 2Department of Clinical Laboratory, Sir Run Run Shaw Hospital, Alaer Hospital, Zhejiang University School of Medicine, Alaer, 843300, People’s Republic of China; 3Department of Infectious Diseases, Sir Run Run Shaw Hospital, Zhejiang University School of Medicine, Hangzhou, 310016, People’s Republic of ChinaCorrespondence: Qiao Yang, Email zjuyangqiao@zju.edu.cnBackground: The co-infection of COVID-19 with community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) is rare but can lead to severe outcomes, especially in diabetic patients with impaired immune function. CA-MRSA, especially PVL-positive strains, can exacerbate COVID-19 symptoms and drive rapid disease progression.Patient and Methods: We present a case of a 53-year-old diabetic female patient with poor glycemic control, who was hospitalized with COVID-19 and rapidly progressed to severe pneumonia. Despite antiviral treatment with Paxlovid and dexamethasone, as well as antimicrobial therapy with piperacillin-tazobactam, her condition deteriorated, leading to respiratory failure requiring extracorporeal membrane oxygenation. A post-mortem sputum culture confirmed MRSA on the day following the patient’s death.Conclusion: This case underscores the critical need for screening and treating bacterial co-infections in COVID-19 management, particularly in immunocompromised hosts, due to the enhanced pathogenicity of CA-MRSA strains. Early recognition and appropriate antimicrobial therapy are essential in reducing the impact of such co-infections.Keywords: COVID-19, methicillin-resistant Staphylococcus aureus, co-infection, diabetes mellitus, pneumonia